Clinical Features of Impacted Common Bile Duct Stones at Duodenal Papilla - Jae Min Lee; Sang Hoon Lee; Ji Hyun Kim; Tae Suk Kim; Sung Hoon Chang; San Ha Kim; Jung Ho Lee; Chang Don Kang; Jin Myung Park (The Korean Journal of Gastroenterology)
Background/Aims: Urgent endoscopic removal is required for gallstones impacted at the duodenal papilla. This study compared the clinical features of impacted papillary stones (IPS) with those of common bile duct stones without impaction. Methods: This study analyzed a common bile duct stone database from 2017 to 2023, identifying patients with IPS. The clinical features of IPS were compared with those of common bile duct stones without IPS (NIPS). Results: One hundred and eighty patients were analyzed; 45 had IPS. The mean age was 63.9 years, with a male predominance in the IPS group. The success rates of selective biliary cannulation were comparable between the IPS and NIPS groups. Multivariate analysis showed that IPS was associated with pancreatitis (odds ratio [OR] 3.78, 95% confidence interval [CI]: 1.17–12.17, p=0.026), bile duct penetrating duodenal wall sign (BPDS, OR 12.09, 95% CI: 3.92–37.33, p<0.001), and the presence of pus (OR 27.05, 95% CI: 4.92–148.85, p<0.001). The periampullary diverticulum (OR 0.28, 95% CI: 0.10–0.82, p=0.021) and the largest stone ≥10 mm (OR 0.31, 95% CI: 0.10–0.96, p=0.043) were inversely correlated with IPS. Conclusions: IPS are associated with pancreatitis, BPDS, and acute suppurative cholangitis, whereas periampullary diverticulum and the stone size are inversely correlated with IPS.